2014
DOI: 10.1016/j.ijscr.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A case of a bleeding benign gastrocolic fistula in 2014

Abstract: HighlightsThe symptoms of gastrocolic fistulae are often undifferentiated.Barium enemas are the most accurate for diagnosis but gastroscopy should be performed to rule out malignancy.The mainstay of treatment of gastrocolic fistulae is surgical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The limited literature on gastrocolonic fistulae suggests barium enemas are the most accurate imaging modality for diagnosis, with a close to 100% detection rate [ 1 , 5 ]. Although the role of CT imaging has not been thoroughly explored in existing literature, CT with oral contrast successfully diagnosed this case with certain similarities existing between this and barium fluoroscopy modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited literature on gastrocolonic fistulae suggests barium enemas are the most accurate imaging modality for diagnosis, with a close to 100% detection rate [ 1 , 5 ]. Although the role of CT imaging has not been thoroughly explored in existing literature, CT with oral contrast successfully diagnosed this case with certain similarities existing between this and barium fluoroscopy modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of CT imaging has not been thoroughly explored in existing literature, CT with oral contrast successfully diagnosed this case with certain similarities existing between this and barium fluoroscopy modalities. By comparison, gastroscopy has a sensitivity of only 30–70% in terms of effective diagnosis, however, following the diagnosis of a fistula, endoscopy with biopsy is recommended to investigate for a malignant aetiology [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The common cause of gastrocolic fistula is different between eastern and western countries. It is reported that gastric cancer is the common cause of gastrocolic fistula in eastern countries, while in western gastrocolic fistula is often caused by colon cancer [4–6] . The most frequent manifestations of gastrocolic fistula are abdominal pain, vomiting with fecal odor, diarrhea, emaciation, anemia, hypoalbuminemia, weight loss and ascites [7] .…”
Section: Introductionmentioning
confidence: 99%